2021
DOI: 10.1186/s43055-021-00521-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung perfusion findings on perfusion SPECT/CT imaging in non-hospitalized de-isolated patients diagnosed with mild COVID-19 infection

Abstract: Background The aim of this retrospective study is to assess the incidence and type of lung perfusion abnormalities in non-hospitalized patients diagnosed with mild COVID-19 infection after de-isolation. Data from 56 non-hospitalized patients diagnosed with COVID-19 infection referred to our nuclear medicine department from July–December 2020 for a perfusion only SPECT/CT study or a ventilation perfusion SPECT/CT study were collected. Images were assessed for the presence and type of perfusion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…(Continued ) [12,20,21,24,[31][32][33]35,37]. These findings can also virtually rule out pulmonary embolisms in these locations.…”
Section: Tablementioning
confidence: 93%
See 1 more Smart Citation
“…(Continued ) [12,20,21,24,[31][32][33]35,37]. These findings can also virtually rule out pulmonary embolisms in these locations.…”
Section: Tablementioning
confidence: 93%
“…Three studies by Evbuomwan et al [24], Mahaletchumy et al [30], and Le Roux demonstrate the risk of a false-positive diagnosis of pulmonary embolism when the ventilation component is omitted. Le Roux et al also reported this in 31% of all patients in which ventilation was needed to rule out false-positive pulmonary embolism [29].…”
Section: Diagnostic Value Of V/q Rather Than Q At Diagnosis Of Pulmon...mentioning
confidence: 99%
“…Clinical reports support similar findings regarding an association between pulmonary hypertension and more severe disease [ 11 ]. Radiological methods including contrast‐enhanced CT, dual‐energy CT (DECT), and single‐photon emission CT (SPECT) combined with CT indicate disturbances in pulmonary blood distribution [ 12 , 13 , 14 , 15 , 16 , 17 ]. The combined impression of unequal blood distribution in single time point scans (DECT) or composite tracer distribution (SPECT) has further support from findings in a case report of an intensive care unit (ICU) patient using dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published data from our facility showed that lung perfusion abnormalities were not uncommon in these patients during the first wave of the pandemic. [17,18] These perfusion abnormalities could be associated with PE, mosaic perfusion, perfusion shunting and pulmonary infiltrates. [17] However, we observed that a subset of these patients had lung perfusion abnormalities that persisted, despite the fact that they had been on long-term anticoagulation therapy.…”
mentioning
confidence: 99%
“…[17,18] These perfusion abnormalities could be associated with PE, mosaic perfusion, perfusion shunting and pulmonary infiltrates. [17] However, we observed that a subset of these patients had lung perfusion abnormalities that persisted, despite the fact that they had been on long-term anticoagulation therapy. This subset of patients also had their perfusion defects matched with a ventilation defect and mosaic hypoattenuation on CT.…”
mentioning
confidence: 99%